Functional role of human interleukin-32 and nuclear transcription factor-κB in patients with psoriasis and psoriatic arthritis - Al-Shobaili, Hani A.; Farhan, Jalees; Zafar, Uzma; Rasheed, Zafar (International Journal of Health Sciences, 2018)
Objective: Inflammation and its associated cell signaling events have been well documented in psoriasis and psoriatic arthritis. However, the potential for interleukin (IL)-32 and its associated signaling to provoke an inflammatory response or to contribute in pathogenesis of psoriasis or psoriatic arthritis are still in early phase. This study determined the role of IL-32 and nuclear transcription factor (NF)-κB in patients with plaque psoriasis and psoriatic arthritis. Methodology: Levels of IL-32 were determined in the plasma samples of patients with plaque psoriasis, psoriatic arthritis and normal healthy subjects by human IL-32 specific Sandwich enzyme-linked immunosorbent assays. To investigate the role of transcription factor in these patients, activated NF-κBp65 levels were determined in the peripheral blood mononuclear cells (PBMCs) by highly sensitive NF-κB transcription factor kit. Results: The levels of IL-32 in the plasma samples of plaque psoriasis or psoriatic arthritis patients were found to be significantly higher as compared with the levels of IL-32 present in the normal human plasma samples (p<0.01). Levels of activated NF-κB were also found higher in plaque psoriasis or psoriatic arthritic patients as compared with the PBMCs of healthy humans (p<0.05). Conclusions: This study shows the role of IL-32 and NF-κB in plaque psoriasis and psoriatic arthritic patients. Results indicate that IL-32 and NF-κB promote inflammation in patients with psoriasis and psoriatic arthritis. Disruption of IL-32 or NF-κB signaling event might provide a novel target for the management of plaque psoriasis and psoriatic arthritis.